Rim-point-column-oriented algorithm in cementless acetabular reconstruction in revision total hip arthroplasty: a minimum five-year follow-up study - Huang, Yong; Zhou, Yixin; Yang, Dejin; Tang, Hao; Deng, Wang; Guo, Shaoyi (The bone & joint journal, 2025)
The Paprosky acetabular defect classification and associated algorithms cannot adequately guide cementless acetabular reconstruction when using porous metal augments. We aimed to introduce a rim, points, and column (RPC)-orientated cementless acetabular reconstruction algorithm, and hypothesized that patients undergoing this treatment would demonstrate satisfactory mid-term clinical and radiological outcomes. We enrolled 114 patients (119 hips) who underwent revision total hip arthroplasty between April 2014 and November 2017 by a single surgeon. A minimum five-year radiological follow-up was available for 90 hips (75.6%), with mean clinical and radiological follow-up durations of 6.8 years (SD 0.9) and 6.3 years (SD 1.9), respectively. Harris Hip Scores improved from 35.4 (SD 10.2) preoperatively to 86.0 (SD 10.3) postoperatively (p < 0.001). Fixation modes included rim fixation (33 hips; 27.7%), three-point fixation without point reconstruction (42 hips; 35.3%), three-point fixation with point reconstruction (40 hips; 33.6%), and three-point fixation with pelvic distraction (four hips; 3.4%). Medial wall reconstruction was performed in 20 patients (16.8%). All acetabular components were radiologically stable. Nine-year Kaplan-Meier survival rates for periprosthetic joint infection, any reoperation, and dissatisfaction were 98.28% (95% CI 88.38 to 99.76), 94.37% (95% CI 81.93 to 98.33), and 95.10% (95% CI 84.64 to 98.50), respectively. Acetabular component stability in cementless acetabular reconstruction relies on rim or three-point fixation, with anterior and posterior column continuity providing essential stability. Medial wall reconstruction complements fixation in the RPC algorithm, yielding satisfactory mid-term outcomes.